Analytical Characterization of USFDA Drug Lorcaserin Recently Banned – Scope for Its Existence in the Pharma Industry: Analytical Characterization of Lorcaserin - Chandrasekar, Vinodhini; Jonnalagadda, Ramya; Kalluru, Hindu (Iranian Journal of Pharmaceutical Sciences, 2023)
Lorcaserin is an anti-obesity agent used to treat chronic obesity. It is a selective 5-HT receptor agonist. Lorcaserin tablet formulation is not marketed in India but was available in the US and the patent expiration happens to be in 2023, there is greater scope for the launch of generic drugs in India as well as other countries. The literature review reveals that there are several clinical data for the estimation of Lorcaserin was reported so far but there are few Analytical reports available. Therefore, the attempt at method development and validation of Lorcaserin raw material was undertaken by various analytical methodologies such as Titrimetry, UV, and HPLC methods. But Lorcaserin tablet (Belviq) was withdrawn from US Market on Feb 13, 2020, due to cancer risk. In this view, the synthetic mixtures were prepared and evaluated by the proposed HPLC Method. The developed titrimetry, UV, and HPLC methods are easy to perform and specific to Lorcaserin and pay a wider way to the characterization of newer drug substances and formulations.